(untitled) (Praxis Educativa, 2012)
In the investigation project “The continuous Teacher Training and the development of critical reflection” we have analysed the previous knowledge of students from Third Cycle and Polimodal School in different subjects. To do this we have designed instructions and levels of evaluation to read and understand the results. The analysis of data, in the case of History, showed that more than the 80% of students are in high pedagogical risk, understood as that which interferes with the possibility of knowledge construction. The obtained results make us think critically about the possible causes of this situation in which we can observe an important gap between the experts’ opinions and the classroom reality.